Dissecting the Human Nature in Kafka's Metamorphosis - Shrestha, Ravi Kumar (Literary Studies, 2020)
This paper intends to strengthen the relationship between humans and non-humans. So, it searches human nature in the non-human. Human beings dissect animals or non-humans in the science lab whereas in the novella 'Metamorphosis', Franz Kafka dissects human nature in the insect after Gregor’s metamorphosis.